Controlled Surface Morphology and Electrical Properties of Sputtered Titanium Nitride Thin Film for Metal–Insulator–Metal Structures - Dongquoc, Viet; Seo, Dong Bum; Anh, Cao Viet; Lee, Jae Hyun; Park, Jun Hong; Kim, Eui Tae (Applied Sciences (Switzerland), 2022)
Titanium nitride (TiN) is a material of interest for electrodes owing to its high-temperature stability, robustness, low-cost, and suitable electrical properties. Herein, we studied the surface morphology and electrical properties of TiN thin film deposited onto an Si/SiO2 <100> substrate through direct current (DC) sputtering with a high-purity TiN target in an argon-gas environment. The electrical properties and surface morphology of TiN thin film significantly improved with increased source power and decreased working pressure. The improved electrical properties could be attributed to the suppressed secondary phase (Ti2N) formation and the reduced electron scattering on smoother surface. Consequently, high-quality TiN thin film with the lowest resistivity (ρ = 0.1 mΩ·cm) and the smallest surface roughness (RMS roughness, Rq = 0.3 nm) was obtained under the optimized condition. The TiN film was further used as the bottom electrode for a metal–insulator–metal (MIM) capacitor. Results demonstrated that the electrical properties of TiN film were comparable to those of noble-metal thin films. Therefore, the TiN thin film fabricated by DC sputtering method had excellent electrical properties and good Rq, indicating its potential applications in MIM capacitors and Si technology.
Keywords: electrical properties; magnetron sputtering; surface roughness; thin film; titanium nitride